2023
DOI: 10.1210/clinem/dgad290
|View full text |Cite
|
Sign up to set email alerts
|

Rare Heterozygous Loss-of-Function Variants in the Human GLP-1 Receptor Are Not Associated With Cardiometabolic Phenotypes

Abstract: Context Impact of lost GLP-1 receptor function in human physiology. Objective Identify coding nonsynonymous GLP1R variants in Danish individuals to link their in vitro phenotypes and clinical phenotypic associations. Methods We sequenced GLP1R in 8,642 Danish individuals with type 2 diabetes or normal glucose tolerance and examined the ability of nonsynonymou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…No statistical methods were used to pre-determine sample sizes for the association analyses as we used fixed populations, but our sample sizes are similar to or higher than those reported in previous publications 14,34,56 .…”
Section: Power Calculationsmentioning
confidence: 82%
See 1 more Smart Citation
“…No statistical methods were used to pre-determine sample sizes for the association analyses as we used fixed populations, but our sample sizes are similar to or higher than those reported in previous publications 14,34,56 .…”
Section: Power Calculationsmentioning
confidence: 82%
“…Recent studies have comprehensively profiled coding GLP1R variants. One study demonstrated no association between variants impairing cAMP signalling and cardiometabolic phenotypes 34 . However, upon inclusion of expression, a recent study revealed an association between reduced cell surface expression and metabolic phenotypes 14 .…”
Section: Nature Metabolismmentioning
confidence: 99%